The Characterizations and Moral development of the Main character in The Nightingale Novel - Komang Trie Nanda Pertiwi; I Nyoman Aryawibawa; Galuh Febri Putra (Pusat riset dan Inovasi Nasional, 2025)
This study explores the character development of Vianne Mauriac in Kristin Hannah’s historical novel The Nightingale, with a particular focus on how her moral progression is revealed through characterization. It aims to examine how direct and indirect characterization contribute to the portrayal of Vianne’s evolving moral reasoning under the pressure of wartime experiences. Employing a descriptive qualitative method, the analysis uses Rimmon-Kenan’s theory to identify characterization techniques and Kohlberg’s stages of moral development to interpret Vianne’s ethical transformation. The findings indicate that Vianne shifts from self-preserving and fear-driven decisions to socially conscious choices and ultimately to morally autonomous actions grounded in universal principles. Her characterization, through action, speech, appearance, and environment, functions not only to construct Vianne’s identity but also to trace her moral journey. Her development demonstrates how literature, particularly historical fiction, can reflect and explore complex ethical growth. The study contributes to understanding how characterization and moral development work together in shaping a compelling and morally resonant protagonist.